FANDOM


Strong D Function

The strong D function is based on a weaker deeply nested Ackermann function called d. The rules are similar with the significant change being that the D function:

\(D(x_1,x_2,x_3,x_4,...,x_n)\)

expands to this function:

\(D(x_1-1,D(x_1,x_2,x_3,x_4,...,x_n-1),...,D(x_1,x_2,x_3,x_4,...,x_n-1))\)

The same expansion is used to replace each input parameter \(x_2\) to \(x_n\). Also refer to the Leading and Trailing Zero rules: L1 and T1, for more information.


Definition

For 2 parameters, the D function is equivalent to the d function:

\(d(a,b)=d(a-1,d(a,b-1))=D(m,n)=D(m-1,D(m,n-1))\)

For 3 parameters, the D function quickly dominates the weaker d function:

\(d(a,b,c)=d(a-1,d(a,b-1),d(a,b,c-1))\)

\(D(k,m,n)=D(k-1,D(k,m,n-1),D(k,m,n-1))\)


Calculated Examples up to D(3,4)

\(D() = 0\) This is a null function that always returns zero.

\(D(3) = 4\) This is the successor function

\(D(1,2) = 5\) This is the same as d(1,2)

\(D(2,3) = 17\) This is the same as d(2,3)

\(D(3,9) = 1,240,025 >> 1,000,000\)

\(D(3,206) = 122*10^{98} >>\) Googol

\(D(3,4) = 5099 >> f_2(6) = 6.2^6 = 384\)


Calculated Examples up to D(1,0,n)

Using the Comparison Rule C1 \(d(m,n-2+\delta) >> f_{m-1}(n)\) where \(\delta << n\)

\(D(4,1) >> f_{3}(3) = f_{\omega}(3)\)

\(D(4,2) >>\) Googolplex

\(D(4,4) >> f_{3}^3(f_{\omega}(3))\)

\(D(6,1) >> g_1\) where \(g_{64} = G\) Graham's number

\(D(D(4,1),D(4,1)) >> D(f_{\omega}(3)+1,f_{\omega}(3)-2) >> f_{\omega}(f_{\omega}(3)) = f_{\omega}^2(3)\)

\(D(1,0,0) = D(0,D(0,1,1),D(0,1,1)) = D(4,4) >> f_3(6) >> f_{\omega}(3)\)

\(D(1,0,1) = D(0,D(1,0,0),D(1,0,0)) = D(D(4,4),D(4,4)) >> f_{\omega}(f_3(6))\)

\(D(1,0,2) >> f_{\omega}^2(f_3(6)) >> f_{\omega}^2(f_3(3)) >> f_{\omega}^2(f_{\omega}(3)) >> f_{\omega}^3(3) >> f_{\omega+1}(3)\)

\(D(1,0,3) >> f_{\omega}^3(f_3(6))\)

\(D(1,0,4) >> f_{\omega}^4(f_3(6)) >> f_{\omega}^4(4) >> f_{\omega+1}(4)\)

and

\(D(1,0,n+\delta) >> f_{\omega}^n(n) = f_{\omega+1}(n)\) where \(\delta << n\)


Calculated Example for Graham's number

\(D(1,1,0) = D(0,D(1,0,1),D(1,0,1)) = D(1,0,2)\)

\(D(1,1,1) = D(0,D(1,1,0),D(1,1,0)) = D(0,D(1,0,2),D(1,0,2)) = D(1,0,3)\)

\(D(1,1,n) = D(1,0,n+2)\)

\(D(1,2,0) = D(0,D(1,1,2),D(1,1,2)) = D(1,1,3) = D(1,0,5)\)

\(D(1,2,n) = D(1,1,n+3) = D(1,0,n+5)\)

\(D(1,3,n) = D(1,2,n+4) = D(1,1,n+7) = D(1,0,n+9)\)

then

\(D(1,m,n) = D(1,m-1,n+m+1) = ... = D(1,0,n-1+(m+2).(m+1)/2)\)

and

\(D(1,9,9) = D(1,6,36) = D(1,3,54) = D(1,0,63) >> g_{64} = G\) Graham's number


Calculated Examples up to D(2,0,n)

Using \(D(1,0,n-1+(m+2).(m+1)/2)\) we get

\(D(1,2,2) = D(1,0,1+4.3/2) = D(1,0,7) >> f_{\omega+1}(7)\)

then

\(D(2,0,0) = D(1,D(1,2,2),D(1,2,2)) >> D(1,0,D(1,2,2)) >> f_{\omega+1}^2(7)\)

and

\(D(2,0,1) = D(2,D(2,0,0),D(2,0,0)) >> f_{\omega+1}^3(7) >> f_{\omega+1}^3(3) = f_{\omega+2}(3)\)

\(D(2,0,2) >> f_{\omega+1}^4(7) >> f_{\omega+1}^4(4) = f_{\omega+2}(4)\)

\(D(2,0,3) >> f_{\omega+1}^5(7) >> f_{\omega+1}^5(5) = f_{\omega+2}(5)\)

and

\(D(2,0,n-2) >> f_{\omega+2}(n)\) when \(n < 7\)

or

\(D(2,0,n-2+delta) >> f_{\omega+2}(n)\) when \(\delta << n\)


Calculated Examples up to D(n,0,n)

\(D(2,3,3) = D(2,0,2+5.4/2) = D(2,0,12) >> f_{\omega+2}(13)\)

then

\(D(3,0,0) = D(2,D(2,3,3),D(2,3,3)) >> D(2,0,D(2,3,3)) >> f_{\omega+2}^2(13)\)

and

\(D(3,0,1) >> f_{\omega+2}^3(13) >> f_{\omega+3}(3) = f_{\omega.2}(3)\)

\(D(3,0,2) >> f_{\omega+2}^4(13) >> f_{\omega+3}(4)\)

and

\(D(3,0,n-2) >> f_{\omega+3}(n)\) when \(n < 13\)

or

\(D(3,0,n-2+\delta) >> f_{\omega+3}(n)\) when \(\delta << n\)

then

\(D(4,0,n-2+\delta) >> f_{\omega+4}(n)\)

and

\(D(n,0,n-2+\delta) >> f_{\omega+n}(n) = f_{\omega.2}(n)\) where \(\delta << n\)


Calculated Examples up to D(n,0,0,n)

\(D(1,0,0,0) = D(0,D(0,1,1,1),D(0,1,1,1),D(0,1,1,1))\)

\(= D(D(1,1,1),D(1,1,1),D(1,1,1)) >> f_{\omega.2}(D(1,1,1)) = f_{\omega.2}(D(1,0,3)) >> f_{\omega.2}(f_{\omega}^3(f_3(6)))\)

\(D(1,0,0,1) >> f_{\omega.2}^2(n)\) where \(n <= f_{\omega}^3(f_3(6))\)

then

\(D(1,0,0,n-1+\delta) >> f_{\omega.2}^n(n) >> f_{\omega.2+1}(n)\) where \(\delta << n\)

\(D(2,0,0,n-2+\delta) >> f_{\omega.2+2}(n)\) where \(\delta << n\)

\(D(3,0,0,n-2+\delta) >> f_{\omega.2+3}(n)\) where \(\delta << n\) or \(f_{\omega^2}(3)\) when \(n = 3\)

and

\(D(n,0,0,n) >> f_{\omega.2+n}(n) >> f_{\omega.3}(n)\) where \(\delta << n\)

Strong D Function Growth Rate

Using subscript notation \(0_{[n-1]}\) to represent n-1 input parameters with value 0:

\(D(1,0,0,0,n) = D(1,0_{[3]},n) >> f_{\omega.3+1}(n)\)

\(D(n,0_{[3]},n) >> f_{\omega.4}(n)\) or \(f_{\omega^2}(4)\) when \(n = 4\)

then

\(D(n,0_{[4]},n) >> f_{\omega.5}(n)\) or \(f_{\omega^2}(5)\) when \(n = 5\)

and

\(D(n,0_{[n-1]},n) >> f_{\omega.n}(n) = f_{\omega^2}(n)\)


Some calculations for n=2

\(D(2,0) = 8 = f_2(2) = f_{\omega}(2)\)

\(D(2,0,2) >> D(2,0,0) >> f_{\omega^2}(2) = f_{\omega^{\omega}}(2) = f_{\epsilon_0}(2)\)


Some calculations for n=3

\(D(4,1) >> f_{\omega}(3)\)

\(D(1,0,2) >> f_{\omega+1}(3)\)

\(D(2,0,1) >> f_{\omega+2}(3)\)

\(D(3,0,1) >> f_{\omega.2}(3)\)

\(D(3,0_{[2]},1) = D(3,0,0,1) >> f_{\omega^2}(3)\)

\(D(D(3,0_{[2]},1),0_{[D(3,0_{[2]},1)]},1) >> f_{\omega^2}^2(3)\)


Next - the Alpha Function

My next blog post will introduce a new Alpha function that I have been thinking about.


References

Strong D Function

The following references are outdated because the above proofs and examples are more reliable. Please keep this in mind if you refer to any of these blogs.

Ad blocker interference detected!


Wikia is a free-to-use site that makes money from advertising. We have a modified experience for viewers using ad blockers

Wikia is not accessible if you’ve made further modifications. Remove the custom ad blocker rule(s) and the page will load as expected.